Ni‐Fe‐Cu‐layered double hydroxides as high‐performance electrocatalysts for alkaline water oxidation. (28th April 2021) - Enhtuwshin, Enhbayar; Mhin, Sungwook; Kim, Kang Min; Ryu, Jeong Ho; Kim, So Jung; Jung, Sun Young; Kang, Sukhyun; Choi, Seunggun; Han, HyukSu
Summary: Alkaline oxygen evolution reaction (OER) electrocatalysts have been widely studied for improving the efficiency and green hydrogen production through electrochemical water splitting. Currently, iron‐doped nickel‐LDHs (NF‐LDHs) are regarded as the benchmark electrocatalyst for alkaline OER, primarily owing to the physicochemical synergetic effects between Ni and Fe. Here, the third element addition into NF‐LDHs is designed to further enhance the electrocatalytic performance through the modulation of electronic property. Cu‐doped NF‐LDHs (NFC‐LDHs) are developed with the self‐supported structure on porous supports. NFC‐LDHs can be grown on carbon cloth (CC) in an intriguing 2D nanosheet structure, wherein the surface electronic configuration is suitably modulated by interactions among Ni‐Fe‐Cu. Importantly, activation energy for OER can be lowered by adding Cu into NF‐LDHs. Thereby, the NFC‐LDHs exhibited enhanced OER activity and improved stability than those of nickel‐LDHs (Ni‐LDHs) and NF‐LDHs. For NFC‐LDHs, small overpotentials of only 230 and 250 mV yield current densities of 50 and 100 mA cm −2, respectively. In addition, excellent electrochemical stability is demonstrated during long‐term OER tests without any degradation demonstrating no dissolution of active metals water electrolysis due to synergetic effects among Ni‐Fe‐Cu. Abstract : A self‐supported Cu‐doped nickel‐iron LDHs (NFC‐LDHs) is developed as a high‐performance OER electrocatalyst. NFC‐LDHs only requires 250 mV overpotentials for generating current density of 00 mA cm −2, which outperforms most of recently reported transition metal‐based electrocatalyts and the benchmark RuO2 catalyst.